PENGARUH LABA DAN ARUS KAS TERHADAP KONDISI FINANCIAL DISTRESS - Hariyanto, Mamang (Fakultas Ekonomi, Program Studi Akuntansi, 2018)
The company's inability to anticipate global developments by strengthening management fundamentals will lead to a reduction in business volume that ultimately leads to corporate bankruptcy. This study aims to examine the effect of earnings and cash flow on the condition of financial distress in various industry sectors industry and consumer goods industry sector listed in Indonesia Stock Exchange. This study uses secondary data obtained from the company's financial statements for the period of 2013 to 2016 listed on the Indonesia Stock Exchange. Data in 2013, 2014, and 2015, 2016 are used to predict financial distress. The results of this study indicate that earnings and cash flow does not have a significant effect on the financial distress in the various industrial sectors of industry and consumer goods industry sector listed on the Indonesia Stock Exchange either partially or simultaneously. Advice to the next researcher is expected to add other financial ratios as independent variables, because it is possible other financial ratios that are not included in this study affect the condition of financial distress.